The Effect of Guided Inquiry Learning Model on Student’s Scientific Communication Skills in SMPN 1 Gempol: Pengaruh Model Inkuiri Terbimbing Terhadap Keterampilan Komunikasi Ilmiah Siswa di SMPN 1 Gempol - Firdausia Amanda Ari Octaviani; Ria Wulandari (Academia Open, 2024)
One of the important skills to develop is scientific communication skills, communication is very important in everyday life. This research aims to determine the effect of the guided inquiry learning model on the scientific communication skills of class VII students at SMPN 1 Gempol, Pasuruan Regency. This research is a quasi-experiment conducted with a posttest-only design. The research sample was class VII D students as the experimental class and class VII C students as the control class with each class having 32 students. In this study, environmental pollution material was used in the experimental class, which was treated using the guided inquiry learning model, while the control class used the learning model commonly used by teachers at the school. The results of the research show that there are significant differences in value and influence in the guided inquiry learning model on written and oral scientific communication skills. Highlights: Guided Inquiry Impact: Examines effect on scientific communication skills. Quasi-Experiment Framework: Utilizes posttest-only design for structured assessment. Written and Oral Proficiency: Highlights impact on both communication modes. Keywords: Guided Inquiry, Written Communication Skills, Oral Communication Skills